Laparoscopic treatment of recurrent and chemoresistant cesarean scar choriocarcinoma. Issue 3 (18th January 2021) - Bakır, Mehmet Sait; Birge, Özer; Karadag, Ceyda; Doğan, Selen; Simsek, Tayup
Abstract: Depending on the developing laparoscopic technique and experience, the treatment of cesarean scar choriocarcinoma can be safely performed laparoscopically by experts. Abstract : Depending on the developing laparoscopic technique and experience, the treatment of cesarean scar choriocarcinoma can be safely performed laparoscopically by experts.